The Sword of Lord and Gideon A Catalogue of Historical Objects Related to the Battle of King's Mountain - Kelly, James C. (Appalachian State University, 1980)
This catalogue of objects related to the Battle of King's Mountain was published as a way to commemorate the battle's bicentenary. The objects included in the catalogue belong to various individuals and institutions; in particular, the D.A.R. Museum, King's Mountain National Military Park, the National Museum of History and Technology, the North Carolina Museum of History, the Rocky Mount Overmountan Museum, the Tennessee Historical Society, and the Tennessee State Museum.